Can post stroke walking improve via telerehabilitation? A systematic review in adults with stroke - Deshmukh, Shravni; Madhavan, Sangeetha (Frontiers in Rehabilitation Sciences, 2023)
Objectives: The purpose of this systematic review is to analyze primary studies investigating the effects of telerehabilitation on walking outcomes for the treatment of adult stroke survivors. Methods: Data sources included PubMed, Embase and CINAHL searched until August 2022, using combinations of several keywords such as “telerehabilitation”, “stroke”, and “gait”. Studies were required to have bidirectional form of videoconferencing with assessor presence, and include assessment of walking function (speed, endurance and/or balance). Data extraction was performed from each full text by one author, and quality and bias were assessed using the Physiotherapy Evidence Database (PEDro). Results: Eight studies involving 248 participants met the inclusion criteria. Seven studies reported significant improvements in outcomes of balance and two showed improvements in endurance. Two studies observed greater balance improvements in the telerehabilitation group compared to control and/or in-person therapy. Differences in frequency, training duration, intervention type, and absence of an in-person therapy control group were identified as causes of variation between studies. Conclusions: We could not reach a definite conclusion regarding telerehabilitation as an effective mode of therapy for walking as most studies did not measure walking speed or endurance. However, strong evidence was found for the use of telerehabilitation for balance improvements, which has implications for walking recovery. Impact Statement: Telerehabilitation appears to be safe, feasible and demonstrated high adherence. Our results highlighted limited studies using real-time supervision to administer telerehabilitation and lack of studies focusing on outcomes of walking speed and endurance, which is needed to fully determine the role of telerehabilitation for gait recovery.